2022
DOI: 10.1038/s41467-022-32597-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for polysaccharide recognition and modulated ATP hydrolysis by the O antigen ABC transporter

Abstract: O antigens are ubiquitous protective extensions of lipopolysaccharides in the extracellular leaflet of the Gram-negative outer membrane. Following biosynthesis in the cytosol, the lipid-linked polysaccharide is transported to the periplasm by the WzmWzt ABC transporter. Often, O antigen secretion requires the chemical modification of its elongating terminus, which the transporter recognizes via a carbohydrate-binding domain (CBD). Here, using components from A. aeolicus, we identify the O antigen structure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The two resolved glycolipid-bound states suggest different ligand-binding sites and/or ATP-independent migration of the substrate within the canyon. Because KpsM is structurally similar to Wzm of the O-antigen ABC transporter, it is possible that KpsMT adopts a similar channel-forming conformation to that of WzmWzt during CPS export 12 , 33 (Fig. 5 and Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two resolved glycolipid-bound states suggest different ligand-binding sites and/or ATP-independent migration of the substrate within the canyon. Because KpsM is structurally similar to Wzm of the O-antigen ABC transporter, it is possible that KpsMT adopts a similar channel-forming conformation to that of WzmWzt during CPS export 12 , 33 (Fig. 5 and Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4h). Extending this KpsM movement could create a channel-forming transporter conformation, as observed for the O-antigen WzmWzt transporter 12,32,33 .…”
Section: Glycolipid Binding To the Kpsm Canyonmentioning
confidence: 95%
“…The last rhamnose residue in this capping unit is O -methylated at the third position. In the E. coli O8 lipopolysaccharide mannan chain, this modification acts as a structural cue for transport across the membrane, thereby terminating polymerisation of the rhamnan chain 45,46 . We therefore propose that a similar mechanism is conserved in Enterococci.…”
Section: Discussionmentioning
confidence: 99%
“…As the CcmAB knockout studies have shown, this does not seem to be indispensable and an arrested CcmCDE complex is still formed 17 , 37 , but this would only require minuscule amounts of heme present in the outer leaflet, which may well be achieved through other pathways or occur spontaneously. Phylogenetically, CcmAB groups with other ABC transporters that act as floppases, with known structures for the O-antigen transporter Wzm-Wzt 41 , and the teichoic acid exporter TarGH 42 . However, we refrain from overstating this analogy, as in the model we present, the cargo would not be transported through the CcmB dimer, but rather along the CcmBC interface.…”
Section: Discussionmentioning
confidence: 99%